Metal film wiring etching solution and preparation method and application thereof

By using specific combinations of chemical components in the chromium etching liquid, the problems of component changes, uneven rate and increased surface roughness during the etching process of the existing chromium etching liquid are solved, and a longer service life and higher etching accuracy are achieved. It is suitable for etching of chromium and chromium composite films of different specifications.

CN118957588BActive Publication Date: 2025-03-11DAGAO IND TECH RES INST (GUANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411331631.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-03-11
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

During the etching process, the components of the existing chromium etching liquid change, the etching rate is uneven, the drilling and surface roughness are prone to increase, and the versatility is poor, making it difficult to meet the development needs of high-finement and large-size.

Method used

The metal film wiring etching solution containing oxide cerium salts, organic sulfonic acids, peroxygen compounds, tranquilizers, functionalized ionic liquids, amino acid-based oligomers, pyrosulfates, alcohol ether solvents and Gemini surfactants is used to realize the long-term life of the etching solution and the high-efficiency etching effect by adjusting the dosage and coordination of each component.

Benefits of technology

It improves the service life and etching accuracy of the etching liquid, ensures that the surface is smooth and without residue after etching, and can effectively etch chromium and chromium composite films of different specifications, improving the versatility and etching effect of the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a metal film wiring etching liquid, an etching method for metal film wiring and an application thereof, and relates to the technical field of etching liquid. Oxidizing cerium salt, organic sulfonic acid, peroxide compound, stabilizer, functionalized ionic liquid, amino acid oligomer, pyrosulfate, alcohol ether solvent, Gemini surfactant and water are used as raw materials, and the raw materials cooperate with each other. The peroxide compound can further oxidize the reduced Ce(III) ions in the etching liquid back to Ce(IV) ions, so as to realize the recycling of Ce(IV) ions, and the long-term service life of the etching liquid is realized by cooperating with alcohol ether solvent and amino acid oligomer. The prepared etching liquid can efficiently etch the chromium metal film wiring structure without the penetration of the photoresist anti-etching layer, which improves the etching technical problem that the existing etching liquid can only meet the requirements of a certain metal film wiring structure, and can be effectively applied to the etching of chromium and chromium composite film process wiring of different specifications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of etching liquid, in particular to a metal film wiring etching liquid and a preparation method and application thereof. Background Art

[0002] Chromium metal is abundant in nature and inexpensive. It is widely used as electrode material, wiring material and mask shielding material in the manufacture of thin-film transistor liquid crystal displays (TFT-LCD) and organic light-emitting diode displays (OLED) because of its corrosion resistance, oxidation resistance, high thermal stability, excellent conductivity, good light-shielding properties and excellent adhesion to other metal and glass substrates.

[0003] With the continuous upgrading of OLED and TTF-LCD device manufacturing technology, there is a demand for high precision and large size development, which puts forward more stringent requirements on the precision of etching and the performance of etching solution. However, the performance of existing chromium etching solution is difficult to meet the requirements, mainly showing several shortcomings:

[0004] (1) The components of the etching solution change during the etching process, which seriously affects the service life of the etching solution;

[0005] (2) The problem of uneven etching rate is prone to occur, which can easily lead to a large amount of side etching and affect the line width accuracy after etching;

[0006] (3) During the etching process, the etching solution easily penetrates and induces undercutting, which increases the surface roughness of the chromium metal film area that does not need to be etched;

[0007] (4) Existing etching solutions can often only meet the requirements of etching a certain type of metal film wiring structure and have poor versatility.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a metal film wiring etching solution and a preparation method thereof, aiming to increase the service life of the etching solution and at the same time improve the etching accuracy so that the surface after etching is smooth and free of residue.

[0010] Another object of the present invention is to provide a method for etching metal film wiring, aiming to improve etching accuracy and make the surface smooth and residue-free after etching.

[0011] Another object of the present invention is to provide a metal film wiring etching solution for use as an electrode material, wiring material or rework in the manufacture of a thin film transistor liquid crystal display or an organic light emitting diode display.

[0012] The present invention is achieved in that:

[0013] In the first aspect, the present invention provides a metal film wiring etching solution, which includes, by mass percentage, 8%-25% of oxidizing cerium salt, 0.5%-9.5% of organic sulfonic acid, 2%-13% of peroxide compound, 0.5%-3.5% of stabilizer, 0.02%-1.0% of functionalized ionic liquid, 0.2%-2.5% of amino acid based oligomer, 0.5%-3.5% of pyrosulfate, 0.8%-5.5% of alcohol ether solvent, 0.05%-2.5% of Gemini surfactant, and the balance is water.

[0014] In an optional embodiment, the composition includes, by mass percentage, 12%-23% oxidizing cerium salt, 2%-8% organic sulfonic acid, 3.5%-11% peroxide compound, 0.8%-2.5% stabilizer, 0.1%-0.85% functionalized ionic liquid, 0.5%-2.0% amino acid oligomer, 0.85%-2.5% pyrosulfate, 1%-4.5% alcohol ether solvent, 0.1%-1.5% Gemini surfactant, and the balance is water.

[0015] In an optional embodiment, the oxidizing cerium salt is selected from at least one of ammonium cerium nitrate, sodium cerium nitrate, potassium cerium nitrate, ammonium cerium sulfate, sodium cerium sulfate and potassium cerium sulfate;

[0016] Preferably, the organic sulfonic acid is selected from at least one of aminosulfonic acid, aminomethanesulfonic acid, hydroxylaminesulfonic acid, isethionic acid and 3-hydroxypropanesulfonic acid;

[0017] Preferably, the peroxy compound is selected from at least one of urea peroxide, peracetic acid, sodium peroxide and sodium percarbonate.

[0018] In an optional embodiment, the stabilizer is selected from at least one of polyethylene glycol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol.

[0019] In an optional embodiment, the functionalized ionic liquid is selected from at least one of an amino-containing functionalized ionic liquid and a hydroxyl-containing functionalized ionic liquid;

[0020] Preferably, the amino-functionalized ionic liquid is selected from at least one of 1-aminoethyl-3-methylimidazolium nitrate, 1-aminoethyl-3-methylimidazolium tetrafluoroborate, 1-aminoethyl-3-methylimidazolium hexafluorophosphate, 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium tetrafluoroborate and 1-aminopropyl-3-methylimidazolium hexafluorophosphate;

[0021] Preferably, the hydroxyl-containing functionalized ionic liquid is selected from at least one of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-hydroxyethyl-3-methylimidazolium hexafluorophosphate, 1-hydroxyethyl-3-methylimidazolium acetate, 1-hydroxyethyl-3-methylimidazolium p-toluenesulfonate, 1-hydroxyethyl-3-methylimidazolium hydrogen sulfate, 1-hydroxyethyl-3-methylimidazolium dihydrogen phosphate, 1-hydroxyethyl-2,3-dimethylimidazolium tetrafluoroborate and 1-hydroxyethyl-2,3-dimethylimidazolium hexafluorophosphate.

[0022] In an optional embodiment, the amino acid-based oligomer is a copolymer of amino acids and organic acids, and has a number average molecular weight of 1500-4500;

[0023] Preferably, the amino acid-based oligomer is selected from at least one of aspartic acid-citric acid copolymer, serine-citric acid copolymer, lysine-citric acid copolymer, cysteine-citric acid copolymer, aspartic acid-malic acid copolymer, serine-malic acid copolymer, lysine-malic acid copolymer and cysteine-malic acid copolymer.

[0024] Amino acid-based oligomers are copolymers prepared by amidation reaction of amino acids, dibasic organic acid malic acid and tribasic organic acid citric acid. The reaction principle is as follows:

[0025]

[0026] Specifically, taking the synthesis of aspartic acid-citric acid copolymer as an example, the amino group in aspartic acid and the carboxyl group in citric acid undergo amidation reaction to obtain aspartic acid-citric acid copolymer. The specific synthesis process is: using diammonium hydrogen phosphate and N,N-dimethylformamide as catalysts (the molar ratio of catalyst to total monomer is 8.5:100) and solvents, respectively, heating and polymerizing in a microwave oven with a power of 1000w for 7-12 minutes to obtain an intermediate product (Formula A); dissolving the cooled intermediate product with a 4mol / L tetramethylammonium hydroxide solution, then filtering, further adjusting the pH value of the supernatant to 3.8-4.4 with hydrochloric acid, and then precipitating with excess anhydrous ethanol, and drying the precipitate in a drying oven at 75°C for 12 hours to obtain an aspartic acid-citric acid copolymer (Formula B).

[0027]

[0028] In an optional embodiment, the pyrosulfate salt is selected from at least one of sodium pyrosulfate, ammonium pyrosulfate and potassium pyrosulfate;

[0029] Preferably, the alcohol ether solvents are selected from at least one of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, triethylene glycol methyl ether, triethylene glycol ethyl ether and triethylene glycol butyl ether;

[0030] Preferably, the Gemini surfactant is selected from at least one of Surfynol420, Surfynol440, Surfynol465 and Surfynol485.

[0031] In a second aspect, the present invention also provides a method for preparing a metal film wiring etching solution in any of the above embodiments, comprising: mixing an oxidizing cerium salt, an organic sulfonic acid, a peroxide compound, a stabilizer, a functionalized ionic liquid, an amino acid-based oligomer, a pyrosulfate, an alcohol ether solvent, a Gemini surfactant, and water according to the composition and ratio of the metal film wiring etching solution;

[0032] Preferably, the mixing temperature is controlled at 20°C-40°C, the stirring speed is 80r / min-200r / min, and the stirring time is 1h-2.5h.

[0033] In a third aspect, the present invention further provides a method for etching metal film wiring, comprising: etching a glass substrate on which a metal film is deposited using the metal film wiring etching solution in any of the above embodiments;

[0034] Preferably, the glass substrate deposited with the metal film is immersed in a metal film wiring etching solution for etching, and the etching temperature is controlled to be 25° C.-55° C., and the etching time is 50 sec.-175 sec.;

[0035] Preferably, the metal film is a chromium or chromium-based composite film, and the thickness of the metal film is 800Å-7500Å.

[0036] In a fourth aspect, the present invention further provides the metal film wiring etching solution in any of the above embodiments for use in electrode material wiring etching, wiring material wiring etching or film stripping and rework in the manufacture of thin film transistor liquid crystal displays or organic light emitting diode displays.

[0037] The present invention has the following beneficial effects: using oxidizing cerium salt, organic sulfonic acid, peroxide compound, stabilizer, functionalized ionic liquid, amino acid oligomer, pyrosulfate, alcohol ether solvent, Gemini surfactant and water as raw materials, and adjusting the dosage of each component, the raw materials cooperate with each other, the peroxide compound can further oxidize the reduced Ce (III) ions in the etching solution back to Ce (IV) ions, realize the recycling of Ce (IV) ions, and further realize the long-term life of the etching solution by coordinating alcohol ether solvent and amino acid oligomer. The etching solution prepared by the present invention can efficiently etch the chromium metal film wiring structure without the penetration of the photoresist anti-etching layer, improves the etching technology problem that the existing etching solution can often only meet the etching of a certain metal film wiring structure, and can be effectively applied to the etching of different specifications of chromium and chromium composite film process wiring. The etching solution prepared by the present invention can adjust the etching rate, etching profile and pattern fineness of the etching solution on metal films of different specifications, and finally obtain the etching effect of low line width loss, good etching cone angle, no metal residue and smooth plane. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0039] The embodiment of the present invention provides a metal film wiring etching solution, which includes, by mass percentage, 8%-25% of oxidizing cerium salt, 0.5%-9.5% of organic sulfonic acid, 2%-13% of peroxide compound, 0.5%-3.5% of stabilizer, 0.02%-1.0% of functionalized ionic liquid, 0.2%-2.5% of amino acid oligomer, 0.5%-3.5% of pyrosulfate, 0.8%-5.5% of alcohol ether solvent, 0.05%-2.5% of Gemini surfactant, and the balance is water.

[0040] It should be noted that the present invention uses oxidizing cerium salt, organic sulfonic acid, peroxide compound, stabilizer, functionalized ionic liquid, amino acid oligomer, pyrosulfate, alcohol ether solvent, Gemini surfactant and water as raw materials, and adjusts the amount of each component, so that the prepared etching solution can regulate the etching rate, etching profile and pattern fineness of the etching solution for metal films of different specifications, and finally obtains low line width loss, good etching cone angle, no metal residue and smooth plane etching effect. The amount of each component is preferably within the above range. If it exceeds the above range, it will have an adverse effect on the etching accuracy and service life, and it is easy to have problems such as uneven surface morphology and residue after etching.

[0041] In a preferred embodiment, by mass percentage, it includes: 12%-23% oxidizing cerium salt, 2%-8% organic sulfonic acid, 3.5%-11% peroxide compound, 0.8%-2.5% stabilizer, 0.1%-0.85% functionalized ionic liquid, 0.5%-2.0% amino acid oligomer, 0.85%-2.5% pyrosulfate, 1%-4.5% alcohol ether solvent, 0.1%-1.5% Gemini surfactant, and the balance is water. By optimizing the amount of each component, the etching accuracy can be further improved and the service life can be extended.

[0042] Oxidizing cerium salt mainly plays the role of oxidizing chromium metal film in acidic environment. Its mass fraction is controlled at 8%-25%. When its mass percentage is lower than 8%, the etching rate of chromium metal film is slow; when its mass percentage is higher than 25%, it will cause excessive chromium etching rate and cause etching to be out of control, and the fineness of the circuit after etching will be significantly reduced. Specifically, based on the total mass fraction of the etching solution as 100%, the weight component of the oxidizing cerium salt can be typically but not limited to 8%, 8.2%, 8.5%, 8.7%, 9%, 9.2%, 9.5%, 9.7%, 10%, 10.2%, 10.5%, 10.7%, 11%, 11.2%, 11.5%, 11.7%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 23%, 24% or 25%, etc.

[0043] In some embodiments, the oxidizing cerium salt is selected from at least one of ammonium cerium nitrate, sodium cerium nitrate, potassium cerium nitrate, ammonium cerium sulfate, sodium cerium sulfate and potassium cerium sulfate. The oxidizing cerium salt can be any one or more of the above, preferably ammonium cerium nitrate or a combination of ammonium cerium nitrate and ammonium cerium sulfate.

[0044] The main function of organic sulfonic acid is to provide an acidic environment for oxidizing cerium salts such as ammonium cerium nitrate to exert their strong oxidizing properties, inhibiting the hydrolysis reaction of oxidizing cerium salts and causing the adverse consequences of reduced oxidation performance. In addition, organic sulfonic acid can also dissolve chromium and chromium oxides, thereby further increasing the reaction rate, reducing etching residues and inhibiting the increase of surface roughness.

[0045] The mass fraction of the organic sulfonic acid is 0.5%-9.5%. Taking the total mass fraction of the etching solution as 100%, the weight components of the organic sulfonic acid may be typically but not limited to 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 4.9%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%. %, 5.2%, 5.4, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8.0%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9.0%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, etc.

[0046] In some embodiments, the organic sulfonic acid is selected from at least one of aminosulfonic acid, aminomethanesulfonic acid, hydroxylaminesulfonic acid, isethionic acid and 3-hydroxypropanesulfonic acid, and the organic sulfonic acid can be any one or more of the above, and the above organic sulfonic acids can increase the reaction rate, reduce etching residues and inhibit the increase of surface roughness. The organic sulfonic acid is preferably aminosulfonic acid, hydroxylaminesulfonic acid or a compound of aminosulfonic acid and hydroxylaminesulfonic acid.

[0047] Peroxide compounds have the effect of synergizing oxidizing cerium salts to oxidize chromium metal films. At the same time, they can further oxidize the reduced Ce(III) ions in the etching solution back to Ce(IV) ions, thereby realizing the recycling of Ce(IV) ions, achieving the purpose of regenerating reactants and extending the service life of etching.

[0048] The mass fraction of the peroxide compound is 2%-13%. Taking the total mass fraction of the etching solution as 100%, the weight component of the peroxide compound can be typically but not limited to 2%, 2.2%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.2%, 4.5%, 4.7%, 5%, 5.5%, 5.7%, 6%, 6.2%, 6.5%, 6.7%, 7%, 7.2%, 7.5%, 7.7%, 8%, 8.2%, 8.5%, 8.7%, 9%, 9.2%, 9.5%, 9.7%, 10%, 10.2%, 10.5%, 10.7%, 11%, 11.2%, 11.5%, 12%, 13%, etc.

[0049] In some embodiments, the peroxide compound is selected from at least one of urea peroxide, peracetic acid, sodium peroxide and sodium percarbonate, and the peroxide compound can be any one or more of the above, and the above peroxide compounds can extend the etching service life. The peroxide compound is preferably urea peroxide, sodium percarbonate or a compound of urea peroxide and sodium percarbonate.

[0050] The stabilizer mainly improves the stability of peroxide compounds in the etching solution and inhibits their own decomposition, thereby further maintaining the stability and service life of the etching solution. The mass fraction of the stabilizer is

[0051] 0.5%-3.5%. When its mass percentage is lower than 0.5%, it cannot stabilize the peroxide compounds due to its too low content, and the fineness of the circuit after etching is significantly reduced; when its mass percentage is higher than 3.5%, the etching performance decreases. Taking the total mass fraction of the etching solution as 100%, the weight component of the stabilizer can be typically but not limited to 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.45%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2, 3.3%, 3.4% or 3.5%, etc.

[0052] In some embodiments, the stabilizer is selected from polyethylene glycol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol. At least one of the stabilizer can be any one or more of the above, and the above stabilizers can all play a role in stabilizing the efficacy of peroxy compounds and can inhibit the decomposition of peroxy compounds themselves. The stabilizer is preferably polyethylene glycol, and specifically at least one of polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 400, polyethylene glycol 500, polyethylene glycol 600, and polyethylene glycol 800 can be selected.

[0053] Functionalized ionic liquids have the effect of inhibiting lateral corrosion and cooperating with amino acid oligomers to improve the complexing ability of chromium ions, thereby further extending the life of the etching solution. The functionalized ionic liquid is selected from at least one of amino-containing functionalized ionic liquids and hydroxyl-containing functionalized ionic liquids, and can be any one or more of the above. The amino group or hydroxyl group in the functionalized ionic liquid can form a chemical bond with the surface of the chromium metal film, so that it can adhere to the chromium metal film during the etching process to form a protective film. At the same time, the ionic liquid has a large-volume steric hindrance structure, which can reduce the etching solution's attack on the lateral chromium metal surface, thereby playing a role in controlling line width loss. In addition, the hydroxyl or amino functional group in the functionalized ionic liquid can form a complex with the chromium metal ion to reduce the concentration of free metal ions, thereby maintaining the stability and service life of the etching solution.

[0054] The mass fraction of the functionalized ionic liquid is 0.02%-1.0%. When the mass percentage is lower than 0.02%, the lateral corrosion degree in the etching process cannot be effectively controlled, and over-etching is likely to occur, thereby causing defects such as circuit short circuits. When the mass percentage is higher than 1.0%, the chromium metal film layer may produce metal residues due to insufficient etching, thereby causing the risk of electrical short circuits. Taking the total mass fraction of the etching solution as 100%, the weight component of the functionalized ionic liquid can be typically but not limited to 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1%, etc.

[0055] In some embodiments, the amino-functionalized ionic liquid is selected from at least one of 1-aminoethyl-3-methylimidazolium nitrate, 1-aminoethyl-3-methylimidazolium tetrafluoroborate, 1-aminoethyl-3-methylimidazolium hexafluorophosphate, 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium tetrafluoroborate and 1-aminopropyl-3-methylimidazolium hexafluorophosphate, and the amino-functionalized ionic liquid can be any one or more of the above.

[0056] In some embodiments, the hydroxyl-functionalized ionic liquid is selected from at least one of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-hydroxyethyl-3-methylimidazolium hexafluorophosphate, 1-hydroxyethyl-3-methylimidazolium acetate, 1-hydroxyethyl-3-methylimidazolium p-toluenesulfonate, 1-hydroxyethyl-3-methylimidazolium hydrogen sulfate, 1-hydroxyethyl-3-methylimidazolium dihydrogen phosphate, 1-hydroxyethyl-2,3-dimethylimidazolium tetrafluoroborate and 1-hydroxyethyl-2,3-dimethylimidazolium hexafluorophosphate, and the hydroxyl-functionalized ionic liquid can be any one or more of the above.

[0057] Amino acid-based oligomers have good water solubility. Due to the high density of carboxyl and amino functional groups on their molecular chains, they have stronger complexing and adsorption properties than traditional small molecule carboxylic acid or amino acid complexing agents. They can efficiently capture free metal ions in the etching solution to form complexes, so as to reduce the concentration of free metal ions in the etching solution and significantly reduce the natural decomposition loss of peroxide compounds, thereby achieving the purpose of maintaining the stability of the etching solution and extending the service life of the etching solution. In addition, the amino acid-based oligomers provided by the embodiments of the present invention can ionize and release a large number of hydrogen protons in the carboxylic acid groups, which can balance and maintain the pH fluctuation of the etching solution, and further improve the etching performance and service life of the etching solution in the continuous etching process.

[0058] The mass fraction of the amino acid based oligomer is 0.2%-2.5%. Taking the total mass fraction of the etching solution as 100%, the weight composition of the amino acid based oligomer can be typically but not limited to 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 045%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.45%, 1.5%, 1.6%, 1.65%, 1.7%, 1.75%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4% or 2.5%, etc.

[0059] In some embodiments, the amino acid-based oligomer is a copolymer of amino acids and organic acids, and has a number average molecular weight of 1500-4500, such as 1500, 2000, 2500, 3000, 3500, 4000, 4500, etc. The amino acid-based oligomer is selected from any one or more of aspartic acid-citric acid copolymer, serine-citric acid copolymer, lysine-citric acid copolymer, cysteine-citric acid copolymer, aspartic acid-malic acid copolymer, serine-malic acid copolymer, lysine-malic acid copolymer and cysteine-malic acid copolymer.

[0060] Pyrosulfate mainly promotes etching reaction and increases the solubility of metal salts, so as to increase the metal ion loading capacity of the etching solution system and avoid the metal ions being adsorbed on the substrate to produce residues. The mass fraction of pyrosulfate is 0.5%-3.5%. Taking the total mass fraction of the etching solution as 100%, the weight composition of pyrosulfate can be typically but not limited to 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 3. 45%, 1.5%, 1.6%, 1.65%, 1.7%, 1.75%, 1.8%, 1.85%, 1.9%, 1.95%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 3.4% or 3.5%, etc.

[0061] In some embodiments, the pyrosulfate is selected from at least one of sodium pyrosulfate, ammonium pyrosulfate and potassium pyrosulfate. The pyrosulfate can be any one or more of the above. The pyrosulfate can be any one or more of the above. The pyrosulfate is preferably ammonium pyrosulfate.

[0062] Alcohol ether solvents mainly play the role of increasing the solubility of chromium metal complexes. As the etching reaction proceeds, the chromium ion content in the etching solution will continue to increase, and there will be problems with the precipitation of chromium metal complexes. Adding alcohol ether solvents helps to quickly dissolve the chromium metal complex before it precipitates, thereby increasing the solubility of the complex and avoiding its precipitation and residue, thereby extending the service life of the etching solution.

[0063] The mass fraction of the alcohol ether solvent is 0.8%-5.5%. Taking the total mass fraction of the etching solution as 100%, the weight component of the alcohol ether solvent can be typically but not limited to 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, etc.

[0064] In some embodiments, the alcohol ether solvents are selected from at least one of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, triethylene glycol methyl ether, triethylene glycol ethyl ether and triethylene glycol butyl ether, and the alcohol ether solvents can be any one or more of the above.

[0065] The main function of Gemini surfactant is to reduce the dynamic and static surface tension of the etching solution, so as to improve the affinity and wettability of the etching solution to the metal film to be etched, reduce the mass transfer resistance of the etching solution and improve the diffusion capacity of the etching product in the etching solution, thereby improving the etching uniformity of the etching solution and reducing the etching load effect of different etching areas. The Gemini surfactant has good low-foaming performance and acidic environment stability. In addition, Gemini surfactant also has the effect of reducing the burrs on the etching circuit.

[0066] The mass fraction of the Gemini surfactant is 0.05%-2.5%. Taking the total mass fraction of the etching solution as 100%, the weight component of the Gemini surfactant can be typically but not limited to 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.45%, 1.5%, 1.6%, 1.65%, 1.7%, 1.75%, 1.8%, 1.85%, 1.9%, 1.95%, 2%, 2.1%, 2.2%, 2.3%, 2.4% or 2.5%, etc.

[0067] In some embodiments, the Gemini surfactant is selected from at least one of Surfynol 420, Surfynol 440, Surfynol 465 and Surfynol 485, and the Gemini surfactant can be any one or more of the above. The Gemini surfactant is preferably Surfynol 420, Surfynol 440 or a compound of Surfynol 420 and Surfynol 440.

[0068] The embodiment of the present invention also provides a method for preparing a metal film wiring etching solution, comprising: according to the composition and ratio of the metal film wiring etching solution, mixing an oxidizing cerium salt, an organic sulfonic acid, a peroxide compound, a stabilizer, a functionalized ionic liquid, an amino acid-based oligomer, a pyrosulfate, an alcohol ether solvent, a Gemini surfactant and water, and optimizing the raw materials and the ratio so that the prepared etching solution can adjust the etching rate, etching profile and pattern fineness of the etching solution for metal films of different specifications, and finally obtain an etching effect with low line width loss, good etching cone angle, no metal residue and smooth surface.

[0069] In some embodiments, the mixing temperature is controlled to be 20°C-40°C, such as 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the stirring speed is 80r / min-200r / min, such as 80r / min, 100r / min, 120r / min, 150r / min, 180r / min, 200r / min, etc.; the stirring time is 1h-2.5h, such as 1.0h, 1.5h, 2.0h, 2.5h, etc.

[0070] In actual operation, raw materials meeting the composition of the metal film wiring etching solution can be placed in a PP or PTFE lined liquid preparation kettle with a circulating condensing device and stirred and mixed.

[0071] An embodiment of the present invention also provides a method for etching metal film wiring, comprising: using the above-mentioned metal film wiring etching solution to etch a glass substrate deposited with a metal film. Due to the improvement of the composition of the metal film wiring etching solution, an etching effect with low line width loss, good etching cone angle, no metal residue and smooth surface can be obtained.

[0072] In some embodiments, the glass substrate deposited with the metal film is immersed in a metal film wiring etching solution for etching, the etching temperature is controlled to be 25°C-55°C (preferably 30°C-45°C), and the etching time is 50sec-175sec. By adjusting the etching temperature and time, the etching effect can be further improved.

[0073] Specifically, the etching temperature can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, etc., and the etching time can be 50sec, 80sec, 100sec, 120sec, 150sec, 170sec, 175sec, etc., where sec means second.

[0074] In some embodiments, the metal film is a chromium or chromium-based composite film, such as any one of chromium-aluminum, chromium-nickel, chromium-molybdenum and chromium-niobium alloy films, or any one or more of the above. The thickness of the metal film is 800Å-7500Å, such as 800Å, 1000Å, 1500Å, 2000Å, 2500Å, 3000Å, 3500Å, 4000Å, 4500Å, 5000Å, 5500Å, 6000Å, 6500Å, 7000Å, 7500Å, etc.

[0075] The embodiment of the present invention also provides a metal film wiring etching liquid for electrode material wiring etching, wiring material wiring etching or film stripping and reworking in the manufacture of thin film transistor liquid crystal display (TFT-LCD) and organic light emitting diode display (OLED). Among them, film stripping and reworking refers to removing the metal film on the surface when the etching effect is not good, and returning it for re-preparation to avoid device waste.

[0076] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0077] Examples 1-12 and Comparative Examples 1-11

[0078] Examples 1-12 and Comparative Examples 1-11 respectively provide metal film wiring etching solutions. The compositions of Examples 1-12 are shown in Table 1, and the compositions of Comparative Examples 1-11 are shown in Table 2.

[0079] Table 1 Etching solution composition in Examples 1-12

[0080]

[0081] Table 2 Etching solution composition in Comparative Examples 1-11

[0082]

[0083] Explanation of the raw materials in Table 1:

[0084] Y1-cerium ammonium nitrate;

[0085] Y2-cerium ammonium sulfate;

[0086] H1─aminosulfonic acid;

[0087] H2─ Hydroxylamine sulfonic acid;

[0088] G1─Urea peroxide;

[0089] G2─sodium percarbonate;

[0090] PEG600─Polyethylene glycol 600;

[0091] TEG─triethylene glycol;

[0092] L1─1-aminoethyl-3-methylimidazolium tetrafluoroborate;

[0093] L2─1-Hydroxyethyl-3-methylimidazole hydrogen sulfate;

[0094] A1─Aspartic acid-citric acid copolymer, M n =3500

[0095] A2─Aspartic acid-malic acid copolymer, M n =3500.

[0096] APS─ammonium pyrosulfate;

[0097] 2-BE─ethylene glycol butyl ether;

[0098] DBG─Diethylene glycol butyl ether;

[0099] Ge1─Surfynol420;

[0100] Ge2─Surfynol440.

[0101] The methods for preparing the etching solutions provided in the above embodiments and comparative examples include the following steps:

[0102] According to the material formula and mass ratio, oxidizing cerium salt, organic sulfonic acid, peroxide compound, stabilizer, functionalized ionic liquid, amino acid-based oligomer, pyrosulfate, alcohol ether solvent, Gemini surfactant and ultrapure water are weighed and mixed to obtain a metal film wiring etching solution; the components of the etching solution are placed in a PP or PTFE-lined liquid preparation kettle with a circulating condensing device and stirred and mixed, the kettle liquid temperature is controlled at 30°C, the stirring speed is 100r / min, and the stirring time is 1.5h.

[0103] In order to compare the technical effects of the embodiments and comparative examples, the following experimental examples are specially set up.

[0104] Experimental Example 1-Etching Rate Test

[0105] A chromium metal film layer with a thickness of 480 nm was deposited on a 0.8 mm glass substrate, and an anti-corrosion layer was spin-coated on the chromium metal film and exposed and developed for patterning (specific steps are: ① coating: spin coating positive photoresist; ② pre-baking: the hot plate temperature was controlled at 90° C., and the baking time was 90 seconds; ③ exposure: i-line photolithography machine exposure 80 mj / cm; ④ development: 2.38% TMAH solution development for 60 seconds; ⑤ post-baking: the hot plate temperature was controlled at 110° C., and the baking time was 120 seconds), and then immersed in the chromium etching solution prepared in the embodiment and the comparative example at 40° C. for etching for 1 minute, and then rinsed with water and dried, and the etching amount was measured by a stylus step difference, and the etching rate (unit: nm / min) was calculated as follows: etching rate = etching amount / etching time.

[0106] Experimental Example 2-Etching Effect Test

[0107] A chromium metal film layer with a thickness of 480 nm was deposited on a glass substrate, a photoresist layer was spin-coated on the chromium metal film, and then exposed and developed for patterning, and then immersed in the chromium etching solution prepared in the embodiment and the comparative example at 40°C for etching for 1.2*JET (JET is the etching time just completed) multiples, and then rinsed with water and dried. A portion of the substrate was observed by a scanning electron microscope for slice cross-section and CD losses were measured, and a portion was stripped with a photoresist stripping solution and washed and dried with water, and the metal residue, edge burrs, chromium metal line surface smoothness and photoresist penetration were observed by a scanning electron microscope. The evaluation criteria are as follows:

[0108] Metal residue evaluation: △-no residue; ▲-a small amount of residue; ╳-a large amount of residue;

[0109] Line edge burr evaluation: ○-no obvious burr; ●-slight burr; ╳-significant burr or defect;

[0110] Single-side CD loss evaluation: I-CD loss≤0.3um; II-0.3um<CD loss≤0.4um; III-CDloss>0.4um;

[0111] Surface smoothness: ☆-no obvious surface defects; ★-small surface roughness; ╳-large surface roughness;

[0112] Penetration of the anti-etching layer: □-no obvious penetration marks; ■-a small amount of penetration marks; ╳-a large amount of penetration marks.

[0113] Table 3 Etching rate and etching effect test results of the etching solutions of the embodiments and comparative examples

[0114]

[0115] It can be seen from Table 3 that the comprehensive performance of Comparative Examples 1-11 is significantly worse than that of Examples 1-11, and the Comparative Examples may have metal residues, burrs on the edges, decreased surface smoothness, penetration marks, etc.

[0116] Experimental Example 3- Etching Solution Life Test

[0117] Chromium powder was added to the etching solutions of Examples 1-3, Example 12, Comparative Example 4, Comparative Example 7 and Comparative Example 11 for dissolution, and the chromium content concentration in the etching solution was controlled to be 500 ppm for each increase in the chromium metal film layer. The etching time was controlled to be 1.2*JET, and the etching temperature was controlled to be 40°C. As the chromium concentration increased, when the etching effect did not meet the required requirements (no etching residue, no obvious penetration, no obvious defects in the chromium metal wire, single CD loss ≤ 0.4), it was considered that the copper ion content had exceeded its lifespan.

[0118] Experimental Example 4-Etching Solution Stability Test

[0119] 6000 ppm of chromium powder was slowly added to the etching solutions of Examples 1-3, Example 12, Comparative Example 4, Comparative Example 7 and Comparative Example 11 respectively to fully dissolve the chromium powder, and then the etching solution samples were left to stand at room temperature for 72 hours to observe whether crystals were precipitated.

[0120] Table 4 Etching solution life and stability test results

[0121]

[0122] It can be seen from the results in Table 3 and Table 4 that the etching solutions of Examples 1-12 of the present invention all exhibit good etching performance, without the occurrence of metal residue, line edge burrs, excessive single-sided CD loss, corrosion resistant layer penetration, and increased wiring surface roughness.

[0123] It can be seen from Example 1 and Comparative Example 1 that when the content of the organic sulfonic acid component in the etching solution is low, the oxidizing ability of the oxidizing cerium salt will be insufficient due to the insufficient acidic environment in the etching solution. In addition, the organic sulfonic acid has the function of dissolving chromium and chromium oxide. When the system organic sulfonic acid is low, it will cause the etching rate to slow down, prolong the immersion time of the corrosion-resistant layer in the etching solution, and then cause the undesirable phenomenon of the penetration of the etching solution and the increase of the roughness of the metal surface; further comparison of Example 1 and Comparative Example 2 shows that when the organic sulfonic acid content is too high, it will also cause the etching rate to be too fast and out of control, and then produce the etching results of excessive etching CD loss and edge burrs. Similarly, the high content of organic sulfonic acid will destroy the molecular chain of the corrosion-resistant layer, and then produce the undesirable results of penetration and increased roughness of the metal surface.

[0124] It can be seen from Example 1 and Comparative Example 3 that the Gemini surfactant plays a positive role in regulating the fineness of the etching circuit and the resistance of the anti-etching layer to the penetration of the etching solution.

[0125] It can be seen from Example 1 and Comparative Example 4 that the etching life of the etching solution of Comparative Example 4 without a stabilizer component is significantly lower, and the stability of the etching solution is significantly reduced.

[0126] By comparing Example 1, Example 3, Comparative Example 5 and Comparative Example 6, it can be seen that the ionic liquid has a significant inhibitory effect on the side etching amount of the wiring during the etching process. The side etching amount of the etching solution of Comparative Example 5 without the ionic liquid component is significantly greater than that of Example 1. If the content of the ionic liquid exceeds the limited content of the present invention, it will also cause the etching rate to slow down and produce etching residues.

[0127] By comparing Example 1, Comparative Examples 7 and 8, it can be seen that Comparative Example 7, in which the content of peroxide compounds is lower than the range specified in the present invention, has a problem of low etching life, while Comparative Example 8, in which the content of peroxide compounds is higher than the range specified in the present invention, shows poor etching effect.

[0128] By comparing the etching results of Example 1, Comparative Example 9 and Comparative Example 10, it can be seen that the oxidized cerium salt has a more obvious effect on the etching rate. When its content is lower than the specified range of the present invention, the etching rate will be slow, and finally the undesirable results of etching residue, corrosion-resistant layer penetration and increased metal surface roughness will be produced; and when the oxidized cerium salt is higher than the specified content range of the present invention, good etching results cannot be obtained.

[0129] By comparing Example 3 and Comparative Example 11, it can be seen that the alcohol ether solvent has a significant effect on the life and stability of the etching solution, and the etching life of the etching solution in Comparative Example 11 which does not use the alcohol ether solvent is significantly lower than that of Example 3, and the stability of the etching solution is deteriorated.

[0130] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A metal film wiring etching solution, characterized in that: Calculated by mass percentage, it includes: 8%-25% oxidizing cerium salt, 0.5%-9.5% organic sulfonic acid, 2%-13% peroxide compound, 0.5%-3.5% stabilizer, 0.02%-1.0% functionalized ionic liquid, 0.2%-2.5% amino acid oligomer, 0.5%-3.5% pyrosulfate, 0.8%-5.5% alcohol ether solvent, 0.05%-2.5% Gemini surfactant, and the balance is water; The oxidizing cerium salt is selected from at least one of ammonium cerium nitrate, sodium cerium nitrate, potassium cerium nitrate, ammonium cerium sulfate, sodium cerium sulfate and potassium cerium sulfate; The organic sulfonic acid is selected from at least one of aminosulfonic acid, aminomethanesulfonic acid, hydroxylaminesulfonic acid, isethionic acid and 3-hydroxypropanesulfonic acid; The peroxy compound is selected from at least one of urea peroxide, peracetic acid, sodium peroxide and sodium percarbonate; The stabilizer is selected from at least one of polyethylene glycol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol; The functionalized ionic liquid is selected from at least one of amino-containing functionalized ionic liquids and hydroxyl-containing functionalized ionic liquids; the amino-containing functionalized ionic liquid is selected from at least one of 1-aminoethyl-3-methylimidazolium nitrate, 1-aminoethyl-3-methylimidazolium tetrafluoroborate, 1-aminoethyl-3-methylimidazolium hexafluorophosphate, 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium tetrafluoroborate and 1-aminopropyl-3-methylimidazolium hexafluorophosphate; the hydroxyl-containing functionalized ionic liquid is selected from at least one of 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-hydroxyethyl-3-methylimidazolium hexafluorophosphate, 1-hydroxyethyl-3-methylimidazolium acetate, 1-hydroxyethyl-3-methylimidazolium p-toluenesulfonate, 1-hydroxyethyl-3-methylimidazolium hydrogen sulfate, 1-hydroxyethyl-3-methylimidazolium dihydrogen phosphate, 1-hydroxyethyl-2 , at least one of 3-dimethylimidazolium tetrafluoroborate and 1-hydroxyethyl-2,3-dimethylimidazolium hexafluorophosphate; The amino acid-based oligomer is a copolymer of amino acids and organic acids, and has a number average molecular weight of 1500-4500; the amino acid-based oligomer is selected from at least one of aspartic acid-citric acid copolymer, serine-citric acid copolymer, lysine-citric acid copolymer, cysteine-citric acid copolymer, aspartic acid-malic acid copolymer, serine-malic acid copolymer, lysine-malic acid copolymer and cysteine-malic acid copolymer; The pyrosulfate is selected from at least one of sodium pyrosulfate, ammonium pyrosulfate and potassium pyrosulfate; The alcohol ether solvents are selected from at least one of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, triethylene glycol methyl ether, triethylene glycol ethyl ether and triethylene glycol butyl ether; The Gemini surfactant is selected from at least one of Surfynol420, Surfynol440, Surfynol465 and Surfynol485.

2. The metal film wiring etching solution according to claim 1, characterized in that Calculated by mass percentage, it includes: 12%-23% oxidizing cerium salt, 2%-8% organic sulfonic acid, 3.5%-11% peroxide compound, 0.8%-2.5% stabilizer, 0.1%-0.85% functionalized ionic liquid, 0.5%-2.0% amino acid oligomer, 0.85%-2.5% pyrosulfate, 1%-4.5% alcohol ether solvent, 0.1%-1.5% Gemini surfactant, and the balance is water.

3. A method for preparing the metal film wiring etching solution according to any one of claims 1 to 2, characterized in that: include: According to the composition and proportion of the metal film wiring etching solution, the oxidizing cerium salt, the organic sulfonic acid, the peroxide compound, the stabilizer, the functionalized ionic liquid, the amino acid-based oligomer, the pyrosulfate, the alcohol ether solvent, the Gemini surfactant and water are mixed.

4. The preparation method according to claim 3, characterized in that: The mixing temperature is controlled at 20°C-40°C, the stirring speed is 80r / min-200r / min, and the stirring time is 1h-2.5h.

5. A method for etching metal film wiring, characterized in that: include: A glass substrate on which a metal film is deposited is etched using the metal film wiring etching solution described in any one of claims 1 to 2.

6. The etching method according to claim 5, characterized in that: The glass substrate deposited with the metal film is immersed in the metal film wiring etching solution for etching, and the etching temperature is controlled to be 25° C.-55° C., and the etching time is 50 sec.-175 sec.

7. The etching method according to claim 6, characterized in that: The metal film is chromium or a chromium-based composite film, and the thickness of the metal film is 800Å-7500Å.

8. The metal film wiring etching solution according to any one of claims 1 to 2 is used for electrode material wiring etching, wiring material wiring etching or film stripping and rework in the manufacture of thin film transistor liquid crystal displays or organic light emitting diode displays.

Citation Information

Patent Citations

  • Chemical conversion treatment solution for magnesium alloy having excellent recycling property, treatment method using the solution and member made of magnesium alloy

    JP2003003275A

  • A Precious Metal Switch Contact Component and Its Preparation Method

    US20160372276A1